Pengaruh Pengumuman Merger dan Akusisi terhadap Abnormal Return Saham Perusahaan Akuisitor dan Non Akuisitor dalam Sektor Industri yang Sama di BEJ Perioda Tahun 1998-2001 - Gunawan, Barbara (Journal of Accounting and Investment, 2005)
The aim of this study was to examine whether mergers and acquisitions were announced by the company akuisitor result in abnormal return for investors. This research using t test analysis in answering the research hypothesis. From the analysis conducted, it was found that a significant abnormal return when information about mergers and acquisitions the company announced. This indicates that merger and acquisition announcements containing charge information for market participants, which is indicated by the Average Abnormal Return significant acquired company's shareholders and non akuisitor akuisitor on announcements about mergers and acquisitions.